Spray forming of bulk ultrafine-grained Al-Fe-Cr-Ti - C. Banjongprasert (2018)
An Al-2.7Fe-1.9Cr-1.8Ti alloy has been spray formed in bulk and the microstructure and properties compared with those of similar alloys produced by casting, powder aomization (PA), and mechanical alloying (MA) routes. In PA and MA routes, a nanoscale metastable icosahedral phase is usually formed and is known to confer high tensile strength. Unlike previous studies of the spray forming of similar Al-based metastable phase containing alloys that were restricted to small billets with high porosity, standard spray forming conditions were used here to produce a ∼98 pct dense 19-kg billet that was hot isostatically pressed ("HIPed"), forged, and/or extruded. The microstructure has been investigated at all stages of processing using scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), and synchrotron X-ray diffraction (XRD) at the Diamond Light Source. Consistent with the relatively low cooling rate in spray forming under standard conditions, the microstructure showed no compelling evidence for the formation of metastable icosahedral phases. Nonetheless, after downstream processing, the spray-formed mechanical properties as a function of temperature were very similar to both PA rapid solidification (RS) materials and those made by MA. These aspects have been rationalized in terms of the typical phases, defects, and residual strains produced in each process route. © 2010 The Minerals, Metals & Materials Society and ASM International.